Antioxidant properties of the Lebanese plant Iris x germanica L. crude extracts and antagonism of chlorpromazine toxicity on Saccharomyces cerevisiae. (4th May 2022) - Sayyed, Katia; Hdayed, Ibrahim; Tabcheh, Mohamad; Abdel-Razzak, Ziad; El-Bitar, Hoda
Abstract: Iris x germanica L., which belongs to the Iridaceae family, has been reported in the literature for its antioxidant properties in acellular chemical-antioxidant assays. Chlorpromazine (CPZ) is an antipsychotic drug known to cause adverse reactions in humans. Oxidative stress is among the main mechanisms by which CPZ exerts its toxicity in animal cell models as well as in the yeast Saccharomyces cerevisiae . In this study we investigated the protective effects of I. germanica L. crude extracts against CPZ toxicity. We demonstrated that methanolic extracts from rhizome (R-M), leaf (L-M) and flower (Fl-M) had potent antioxidant activity by scavenging the free radical DPPH, with half-maximal effective concentrations (EC50 ) 193, 107, and 174 µg/mL, respectively. R-M, L-M and Fl-M at doses up to 1000 µg/mL, didn't affect yeast cell growth. In addition, we demonstrated for the first time that L-M at 1000 µg/mL and R-M at all tested doses counteracted CPZ toxicity, probably by promoting yeast cell antioxidant agents. The R-M capacity to counteract CPZ toxicity was lost in the yeast strain mutant in catalase-encoding gene (Cta1), while strains mutant in Sod2, Skn7 and Rap1 showed mild or full R-M-induced protective effect against CPZ toxicity. Our results demonstrated that I. germanica L. R-M extract counteracted CPZ toxicity in the yeast cell model. Further studies are planned to isolate the involved bioactive compounds and identify the involved genes and the antioxidant agents.